2011
DOI: 10.1039/c1dt11108f
|View full text |Cite
|
Sign up to set email alerts
|

Major impact of N-methylation on cytotoxicity and hydrolysis of salan Ti(IV) complexes: sterics and electronics are intertwined

Abstract: A series of Ti(IV) complexes containing diamino bis(phenolato) "salan" type ligands with NH coordination were prepared, and their hydrolysis and cytotoxicity were analyzed and compared to the N-methylated analogues. Substituting methyl groups on the coordinative nitrogen donor of highly active and stable Ti(IV) salan complexes with H atoms has two main consequences: the hydrolysis rate increases and the cytotoxic activity diminishes. In addition, the small modification of a single replacement of Me with H lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
67
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 41 publications
(81 citation statements)
references
References 32 publications
12
67
2
Order By: Relevance
“…However, recent advances in titanium-stabilizing ligands have led to a new class of cytotoxic Ti-based antineoplastics 5 . Prominently, introduction of the ligand salan, a diamine bisphenalato compound, conferred excellent hydrolytic stability to Ti(IV) alkoxide complexes, as presented by Tshuva and co-workers (Chart 1, 1) [6][7][8][9][10][11][12][13] . Many of these compounds also demonstrated micro-and submicromolar antiproliferative activity against HT29 and OVCAR-1 cancer cell lines in vitro.…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, recent advances in titanium-stabilizing ligands have led to a new class of cytotoxic Ti-based antineoplastics 5 . Prominently, introduction of the ligand salan, a diamine bisphenalato compound, conferred excellent hydrolytic stability to Ti(IV) alkoxide complexes, as presented by Tshuva and co-workers (Chart 1, 1) [6][7][8][9][10][11][12][13] . Many of these compounds also demonstrated micro-and submicromolar antiproliferative activity against HT29 and OVCAR-1 cancer cell lines in vitro.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Previously we have presented the diaminobis(phenolato) Ti IV complexes with particularly high cytotoxic activity, demonstrating higher hydrolytic stability than that of budotitane and titanocene dichloride [14][15][16][17][18][19][20][21][22][23][24][25]. Structure-activity relationship studies revealed that, for example, methyl groups on the nitrogen atoms (N-Me) greatly improve the hydrolytic stability of the complexes compared with no substitution (N-H) [22]. Subsequent studies suggested that the active species are polynuclear O-bridged hydrolysis products [26]: trinuclear species for N-Me complexes [15,16] and binuclear species for N-H complexes [22,23], thus eliminating the need for labile ligands.…”
mentioning
confidence: 98%
“…Complexes of Ti IV , budotitane ((bzac) 2 Ti(OEt 2 ), titanocene dichloride (Cp 2 TiCl 2 ) and their derivatives exhibited high anti-cancer properties against a range of cell lines with relatively minor side effects; nevertheless, rapid hydrolysis of the complexes in biologically relevant solutions to multiple unidentified species inhibited their utility [2][3][4][5][6][7][8][9][10][11][12][13]. Previously we have presented the diaminobis(phenolato) Ti IV complexes with particularly high cytotoxic activity, demonstrating higher hydrolytic stability than that of budotitane and titanocene dichloride [14][15][16][17][18][19][20][21][22][23][24][25]. Structure-activity relationship studies revealed that, for example, methyl groups on the nitrogen atoms (N-Me) greatly improve the hydrolytic stability of the complexes compared with no substitution (N-H) [22].…”
mentioning
confidence: 99%
See 2 more Smart Citations